Effect of tax aggressiveness on CEO turnover - Lopo Martinez, Antonio; Brito, Flavio Oliveira; Chiachio, Viviane Ferreira de Oliveira (RC&C. Revista de Contabilidade e Controladoria, 2021)
This study verifies the influence of corporate tax aggressiveness on replacing the Chief Executive Officer - CEO. Tax Aggressiveness can be a determinant of CEO turnover in companies listed on the Brazilian stock exchange B3. Efficient tax planning is essential for any organization, being a manager's duty to avoid paying unnecessary taxes. Methodologically, the study uses three tax aggressiveness metrics to verify the nature of this relationship from 2010 to 2016, ranking the results by quintile and identifying the high and low extremes of tax aggressiveness. Also, control variables were used to reduce the bias of the proposed regression. Two of the proxies of tax aggressiveness, Cash Effective Tax Rate Long Run Effective Tax Rate, showed significant low tax aggressiveness. The results evidence that less tax aggressive CEOs are more likely to be replaced. For managers, the findings reinforce that tax planning is a determinant factor to remain in the position.